2017
DOI: 10.1159/000475877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Polymyxin E and Polymyxin B as an Additive to Pulmonary Surfactant in Escherichia coli Pneumonia of Ventilated Neonatal Rabbits

Abstract: Background: Ascending maternofetal bacterial infections often result in premature birth and neonatal respiratory distress. These neonates are treated with exogenous pulmonary surfactant (SF) and systemic antibiotics. Polymyxins are antimicrobiotic peptides that may bind to SF phospholipids. Objectives: Does topical administration of SF/polymyxin reduce bacterial growth in neonatal rabbit pneumonia and improve pulmonary function? Methods: Neonatal rabbits were tracheotomized and treated intratracheally with mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The favourable in vitro effect of PxB is explained by its ability to bridge PL membranes, making it easier to develop more-resistant multilayer structures [ 10 ]. PxB also increases the resistance of the surfactant to meconium, and combined treatment with PSUR/PxB is effective against the systemic spread of E. coli [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The favourable in vitro effect of PxB is explained by its ability to bridge PL membranes, making it easier to develop more-resistant multilayer structures [ 10 ]. PxB also increases the resistance of the surfactant to meconium, and combined treatment with PSUR/PxB is effective against the systemic spread of E. coli [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the addition of PxB improves the surface properties of exogenous surfactants and increases the resistance to inactivation with plasma albumin that enters the airspaces and interferes with pulmonary surfactants in the case of alveolar–capillary membrane damage [ 11 ]. The combination of surfactant/PxB or PxE mixtures was also tested in other models of surfactant inhibition, as in meconium aspiration syndrome or neonatal pneumonia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic intratracheal treatment of neonatal rabbits with PxB–EPS prevents the growth of bacterial E. coli and improves lung function in neonatal pneumonia of rabbits . Encouraging results were reported in a similar model of pneumonia with polymyxin E, where the mixing of polymyxin with the surfactant increased its bactericidal effect .…”
Section: Introductionmentioning
confidence: 96%